Peran Ilmu Aṣwāt Dalam Memahami Intonasi dan Jeda Kalimat Bahasa Arab - Lina Marlina; Pajar Abdurahman; Yusri Yusron; Halwa Nida Nur Syariah (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: Ilm al-Aṣwāt, the study of Arabic phonetics and phonology, plays a crucial role in enhancing both fluency and accuracy in spoken communication. This article aims to explore the role of phonetic knowledge in understanding intonation and pause (waqf) in Arabic sentences and its contribution to the development of learners’ communicative competence. Using a literature review approach, this study analyzes recent scholarly works on how intonation distinguishes sentence types (declarative, interrogative, imperative, and prohibitive), and how strategic pauses influence meaning especially within the Qur’anic context. The findings suggest that proper control of intonation and pausing not only strengthens sentence structure but also directly affects meaning, nuance, and message clarity in Arabic discourse. Therefore, integrating the science of aṣwāt into Arabic language instruction is essential to support the formation of comprehensive speaking skills. This study recommends that aṣwāt be taught not merely as a technical discipline but as a pragmatic strategy for developing both linguistic and sociolinguistic competence among learners.Keywords: Ilm al-Aṣwāt, Suprasegmental Phonology, Intonation, Pausing, Arabic Language Abstrak: Ilmu aṣwāt, sebagai kajian fonetik dan fonologi dalam bahasa Arab, memainkan peran vital dalam menunjang kefasihan dan ketepatan komunikasi lisan. Artikel ini bertujuan untuk menelaah secara mendalam bagaimana ilmu aṣwāt berkontribusi dalam memahami intonasi dan jeda kalimat bahasa Arab, serta relevansinya dalam membentuk kompetensi komunikatif pembelajar non-Arab. Melalui pendekatan studi pustaka, dikaji sejumlah literatur terkini yang mengupas fungsi intonasi dalam membedakan jenis kalimat (khabariyyah, istifhāmiyyah, amr, nahy) serta peran jeda (waqf) dalam menghindari ambiguitas makna, khususnya dalam konteks Al-Qur’an. Temuan menunjukkan bahwa ketepatan dalam mengelola intonasi dan jeda tidak hanya memperkuat struktur ujaran, tetapi juga berimplikasi langsung terhadap makna, nuansa, dan keberterimaan pesan dalam komunikasi Arab. Oleh karena itu, integrasi ilmu aṣwāt dalam pembelajaran bahasa Arab merupakan kebutuhan mendesak dalam mendukung pembentukan maharah kalām yang utuh. Penelitian ini merekomendasikan agar ilmu aṣwāt tidak hanya diajarkan secara teknis, tetapi juga dimaknai sebagai strategi pragmatis dalam membangun kompetensi linguistik dan sosiolinguistik pembelajar.Kata kunci: ilmu aṣwāt, fonologi suprasegmental, intonasi, jeda, bahasa Arab